Melting of the snow cover in the Polish Tatra Mountains – long-term changes and the impact of atmospheric circulation - Jankowska, Zuzanna; Falarz, Małgorzata (Quaestiones Geographicae, 2025)
The aim of the research is to present the annual distribution and long-term changes in the melting of the snow cover in the Tatras. An additional aim is to explain the causes of rapid snow cover melt related to atmospheric circulation. The paper uses data from three meteorological stations located at different altitudes in the Polish Tatra Mountains for two periods, 1966–2023 and 1991–2023. The conditional probability was calculated for the occurrence of rapid snow cover melting under different atmospheric circulation conditions. The most important results of the study are as follows: (1) the highest number of days with snow cover melting in the winter season (i.e. snow season) occurred in March in Zakopane, in April in Hala Gąsienicowa and in May on Kasprowy Wierch; (2) statistically significant long-term trends were found mainly for melting rate characteristics (in cm) and in the majority of cases in the period 1966/1967–2022/2023; furthermore, a positive, statistically significant trend in the number of days with snow cover melting was found for Kasprowy Wierch. In the period 1991/1992–2022/2023, one statistically significant trend was detected: a negative tendency in the average seasonal melting of snow cover in Hala Gąsienicowa and (3) rapid melting of snow is favoured by the inflow of tropical air masses over southern Poland, the advection of air from the southern sector with cyclonic conditions and the passage of a warm weather front.